Characterization of Disposable Facemasks for COVID-19 Through Colorimetric Analysis. Issue 1 (1st November 2022) - Fraschetti, E.; Puglisi, D.; Domènech-Gil, G.; Buzzin, A.; Mastrandrea, A.; Mazzetta, I.; de Cesare, G.; Casalinuovo, S.; Quaranta, S.; Caputo, D.
Abstract : Many aspects of the world population's daily life have been recently changed by the events following the SARS-COV-2 pandemic outbreak. Among all the consequences, wearing face masks has become a common routine to protect from virus transmission risks. This work presents a simple colorimetric system able to detect the carbon dioxide (CO2 ) saturation inside a disposable face mask, which is useful to determine the level of wear and degradation and to visually provide indications on its disposal time. The experiments were carried out by wearing a FFP2 face mask externally treated with a phenolphthalein solution and including in its breathing zone a CO2 sensor. Changes in face mask color were recorded by a camera and analyzed with ImageJ. A strong correspondence was found between the high values of CO2 detected by the sensor and the analyzed data. The results are promising and suggest further efforts in developing easy-to-use colorimetric methods as a visual indicator of the life cycle of a disposable face mask.